REKONSTRUKSI FIQH MUAMALAH KONTEMPORER BERBASIS MAQĀṢID AL-SYARĪ‘AH - Rudi Edwaldo Jasmit; Herdifa Pratama; Siti Yulia Makkininnawa; Bobby Ferly; Muhajirin Muhajirin; Landes Yuanda (IAIN BONE, 2026)
Contemporary fiqh muamalah faces significant challenges in response to the development of modern economic practices characterized by transactional complexity, economic digitalization, and unequal economic relations. Within Islamic economic law, the development of fiqh muamalah remains largely dominated by a legal-formalistic approach that emphasizes the textual validity of contracts, while the objectives of Islamic law and the socio-economic impacts of transactions receive limited attention. This condition contributes to the weak realization of substantive justice in contemporary muamalah practices. This paper examines the problem of legal formalism in fiqh muamalah and analyzes the operational limitations of maqāṣid al-sharī‘ah in Islamic economic practice. Employing a normative–conceptual legal approach, the discussion focuses on reconstructing contemporary fiqh muamalah based on maqāṣid al-sharī‘ah by positioning legal objectives as the foundation of legal reasoning. The analysis demonstrates that such reconstruction requires the repositioning of maqāṣid al-sharī‘ah as an epistemological basis, the expansion of legal analysis from contractual relations to economic structures and impacts, and the affirmation of substantive justice as a key criterion of Sharī‘ah compliance. This approach is expected to strengthen the role of fiqh muamalah as a responsive, contextual, and justice-oriented framework within the development of Islamic economic law.